A sheet mortar and a method for preparing the same
By granulating, drying, and pressing wet mixtures into flakes, the problems of slow dissolution of flaky mortar and component separation during transportation are solved, achieving rapid dissolution and efficient construction.
Patent Information
- Application Number
- CN202310921888.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2043-07-26
AI Technical Summary
Existing sheet mortars dissolve slowly during use, resulting in low construction efficiency. Furthermore, they are prone to separation and dust pollution during transportation, failing to meet environmental protection requirements.
The wet mixture is granulated, dried, and then compressed into tablets. The particle size and bulk density of the semi-dry particles are controlled, the solvent content is reduced, and the particles are kept evenly distributed during the tableting process to improve porosity.
It achieves both mechanical strength and environmental performance of sheet mortar during transportation, while also dissolving rapidly during use to improve construction efficiency.
Smart Images

Figure CN117067349B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, in particular to a sheet-shaped mortar and a preparation method thereof. BACKGROUND
[0002] Traditional mortar has two forms: dry-mixed mortar and wet-mixed mortar, and the product states are dry powder and wet slurry, respectively. In the transportation process of the dry-mixed mortar, the components are prone to separate and the uniformity is significantly reduced. In the stirring process, serious dust pollution is caused, which cannot meet the increasingly stringent environmental protection requirements of the country. The wet-mixed mortar has a high transportation cost and needs to be transported to the construction site within a specified time by a special mixing truck.
[0003] There is a sheet-shaped mortar in the prior art. The sheet-shaped mortar presents a fixed sheet shape when not in use, which is beneficial to transportation. When in use, the sheet-shaped mortar can be quickly dissolved into wet slurry by spraying liquid thereon.
[0004] The applicant found in the process of implementing the present application that the existing sheet-shaped mortar is slow to dissolve in the use process due to the product properties, which is not conducive to efficient construction. SUMMARY
[0005] The purpose of the present application is to provide a sheet-shaped mortar and a preparation method thereof to solve the above technical problems in the prior art, mainly including the following two aspects:
[0006] The first aspect of the present application provides a preparation method of a sheet-shaped mortar, including the following steps:
[0007] Step S100, obtaining a wet mixture, wherein the raw materials of the wet mixture include inorganic cementitious materials, aggregates, water-soluble binders and solvents; the wet mixture is granulated to obtain wet granules;
[0008] Step S200, drying the wet granules to obtain semi-dry granules;
[0009] Step S300, tabletting the semi-dry granules to obtain sheet-shaped mortar.
[0010] Further, the semi-dry granules are sieved before tabletting.
[0011] Further, in step S300, the particle size of the semi-dry granules for tabletting is 0.85mm-4.75mm.
[0012] Further, in step S300, the particle size distribution of the semi-dry particles is a first particle size combination or a second particle size combination, the first particle size combination comprising 30 parts by weight to 80 parts by weight of semi-dry particles with a particle size of 0.85 mm to 1.40 mm and 20 parts by weight to 70 parts by weight of semi-dry particles with a particle size of 1.40 mm to 2.00 mm; the second particle size combination comprising 20 parts by weight to 60 parts by weight of semi-dry particles with a particle size of 2.00 mm to 2.80 mm, 15 parts by weight to 50 parts by weight of semi-dry particles with a particle size of 2.80 mm to 4.00 mm, and 25 parts by weight to 65 parts by weight of semi-dry particles with a particle size of 4.00 mm to 4.75 mm.
[0013] Further, the weight percentage of residual solvent in the semi-dry particles is 1% to 10%.
[0014] Further, in step S300, the bulk density of the semi-dry particles is 900 kg / m 3 1800 kg / m 3 .
[0015] Further, in step S300, the bulk density of the semi-dry particles is 1100 kg / m 3 1500 kg / m 3 .
[0016] Further, in step S300, the semi-dry particles and the support are pressed together.
[0017] Further, the support is located on the lower surface and / or the upper surface of the sheet mortar.
[0018] Further, the support is at least one of an inorganic fiber mesh, a polymer mesh, a metal mesh, and a soluble film.
[0019] Further, after the semi-dry particles are pressed, a drying process is performed to obtain the sheet mortar.
[0020] Further, in step S200, the drying temperature is 50°C to 120°C.
[0021] Further, in step S200, the drying temperature is 65°C to 110°C.
[0022] Further, in step S100, a wet mixture is obtained by mixing a dry mixture and a binder solution, the dry mixture comprising inorganic cementitious materials and aggregates, and the binder solution comprising a water-soluble binder and a solvent.
[0023] Further, the dry mixture further comprises at least one of admixtures, additives, and fibers.
[0024] Further, the dry mixture comprises the following raw materials in parts by weight: 15 parts by weight to 70 parts by weight of inorganic cementitious material, 15 parts by weight to 85 parts by weight of aggregate, 0 parts by weight to 50 parts by weight of admixture, 0 parts by weight to 15 parts by weight of additive, and 0 parts by weight to 5 parts by weight of fiber.
[0025] Further, the inorganic cementitious material is at least one of cement, gypsum, lime, geopolymer, calcium silicate-based mineral;
[0026] The aggregate is at least one of natural sand, machine-made sand, expanded perlite, vitrified microbead, hollow glass bead, foamed resin particle, and expanded clay;
[0027] The admixture is at least one of fly ash, slag powder, carbide slag powder, calcined kaolin, coal gangue, silica fume, zeolite powder, desulfurization gypsum, limestone powder, steel slag powder, and phosphorous slag powder;
[0028] The additive is at least one of water-retaining agent, redispersible latex powder, early strength agent, retarder, accelerator, waterproofing agent, water-reducing agent, anti-freezing agent, disintegrant, expanding agent, shrinkage-reducing agent, alkaline activator, and acidic activator;
[0029] The fiber is at least one of carbon fiber, glass fiber, steel fiber, and polymer fiber.
[0030] Further, the weight ratio of the dry mixture and the binder solution is 100:3 to 20.
[0031] Further, the weight ratio of the water-soluble binder and the solvent in the binder solution is 1:2 to 75.
[0032] Further, the solvent is an organic solvent or a mixture of organic solvent and water.
[0033] Further, the solvent is a mixture of organic solvent and water, and the weight ratio of the organic solvent to water is 1:0 to 3.
[0034] Further, the water-soluble binder is at least one of vegetable glue, animal glue, microbial glue, modified starch, modified cellulose, polymeric water-soluble resin, and condensation type water-soluble resin.
[0035] Further, in the step S100, the granulation is any one of extrusion granulation, rotary granulation, and fluidized bed granulation.
[0036] The second aspect of the present application provides a sheet-shaped mortar prepared by the above preparation method.
[0037] The present application has at least the following technical effects relative to the prior art:
[0038] The present application effectively reduces the solvent content in the semi-dry granules, and retains the appropriate compressibility and physical properties, by granulating and drying the wet mixture, and then using it to compress the tablets, and in the tabletting process, the semi-dry granules are uniformly distributed, and the porosity in the tablet is effectively improved after molding, so not only the mechanical strength of the tablet-shaped mortar is ensured during transportation and transfer, but also when the tablet-shaped mortar needs to be dissolved for use, water can quickly enter the inside of the tablet-shaped mortar through the pores, realizing the rapid dissolution of the tablet-shaped mortar, improving the construction efficiency and environmental performance. BRIEF DESCRIPTION OF DRAWINGS
[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments of the present application or the prior art description. Obviously, the drawings described below are only some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained without creative labor on the basis of these drawings.
[0040] Figure 1 is a flow chart of the preparation method of the tablet-shaped mortar of the present application;
[0041] Figure 2 is a flow chart of another preparation method of the tablet-shaped mortar of the present application. DETAILED DESCRIPTION
[0042] The following description provides many different embodiments, or examples, for implementing different features of the present application. Specific examples are described in the following description to provide a thorough explanation of the present application. These examples are not intended to be exhaustive or to be limiting of the scope of the present application. Rather, these examples are intended to be representative of the many embodiments of the present application.
[0043] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the following will combine the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the claimed present application, but only to represent selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0044] Traditional mortar has two forms: dry-mixed mortar and wet-mixed mortar, and the product state is dry powder and wet slurry, respectively. Dry-mixed mortar is prone to component separation and significant decrease in uniformity during transportation, and produces serious dust pollution during stirring, which cannot meet the increasingly stringent environmental protection requirements of the state. Wet-mixed mortar has high transportation cost and needs to be transported to the construction site within a specified time by a special stirring vehicle.
[0045] There is a sheet-shaped mortar in the prior art, which presents a fixed sheet shape when not in use, facilitating transportation, and only needs to be sprayed with a liquid to quickly dissolve into a wet slurry when in use. For the sheet-shaped mortar, the related art usually adopts an extrusion molding method to produce the sheet-shaped mortar, that is, dry powder is mixed with an organic solvent to form a slurry, and then the slurry is directly extruded as a whole to form a sheet-shaped mortar. However, this method has the following outstanding problems: the solvent content in the slurry is high, and the one-time whole extrusion molding leads to a too dense sheet-shaped mortar and a low porosity of the sheet, which makes the sheet dissolve slowly and the construction efficiency is not high.
[0046] To improve the construction efficiency of the sheet-shaped mortar, the present application provides a preparation method of a sheet-shaped mortar, as shown in Figure 1 The method comprises the following steps:
[0047] In step S100, a wet mixture is obtained, and the raw materials of the wet mixture include inorganic cementitious materials, aggregates, water-soluble binders, and solvents. The wet mixture is granulated to obtain wet granules.
[0048] In step S200, the wet granules are dried to obtain semi-dry granules.
[0049] In step S300, the semi-dry granules are tabletted to obtain sheet-shaped mortar.
[0050] By granulating, drying, and then tableting the wet mixture, the solvent content in the semi-dry granules is effectively reduced, and the appropriate compressibility is retained. Meanwhile, the semi-dry granules are uniformly distributed during tableting, and the porosity of the sheet-shaped mortar after molding is effectively improved. Therefore, not only the mechanical strength of the sheet-shaped mortar is ensured during transportation and transfer, but also when the sheet-shaped mortar needs to be dissolved for use, water can quickly enter the interior of the sheet-shaped mortar through the pores to realize rapid dissolution of the sheet-shaped mortar, thereby improving the construction efficiency and environmental performance.
[0051] Controlling the particle size distribution of the semi-dry granules can effectively ensure the porosity and mechanical strength of the sheet-shaped mortar after tableting. Therefore, the semi-dry granules can be sieved before tableting to obtain semi-dry granules with a specified particle size, and the particles with excessively large particle size or broken particles with excessively small particle size that are agglomerated during drying are sieved out.
[0052] Specifically, in step S300, the particle size of the semi-dry particles used for tableting can be controlled to be 0.85 mm to 4.75 mm.
[0053] To further control the porosity, density, and / or mechanical strength of the prepared flaky mortar, in step S300, the particle size distribution of the semi-dry particles can be selected as either a first particle size combination or a second particle size combination. In the first particle size combination, semi-dry particles with a particle size of 0.85 mm to 1.40 mm account for 30 to 80 parts by weight, and semi-dry particles with a particle size of 1.40 mm to 2.00 mm account for 20 to 70 parts by weight. In the second particle size combination, semi-dry particles with a particle size of 2.00 mm to 2.80 mm account for 20 to 60 parts by weight, semi-dry particles with a particle size of 2.80 mm to 4.00 mm account for 15 to 50 parts by weight, and semi-dry particles with a particle size of 4.00 mm to 4.75 mm account for 25 to 65 parts by weight.
[0054] To ensure that the semi-dry granules have appropriate compressibility and meet the requirements for tableting, the weight percentage of residual solvent in the semi-dry granules can be controlled to be 1% to 10%.
[0055] After processing semi-dry granules into sheet mortar, if the density of the sheet mortar is too high, the porosity will decrease accordingly, resulting in a lower dissolution efficiency during construction. Conversely, if the density is too low, the mechanical strength of the sheet mortar will deteriorate. To obtain sheet mortar with suitable density, high porosity, fast dissolution efficiency, and good mechanical strength, the bulk density of the semi-dry granules can be controlled at 900 kg / m³ in step S300. 3 ~1800kg / m 3 .
[0056] Furthermore, in step S300, the bulk density of the semi-dry particles can be controlled to be 1100 kg / m³. 3 ~1500kg / m 3 .
[0057] To improve the mechanical strength of sheet mortar, in step S300, the semi-dry particles and the support can be pressed together into sheets.
[0058] Specifically, the support is located on the lower and / or upper surface of the sheet mortar.
[0059] Specifically, the support is at least one of inorganic fiber mesh, polymer mesh, metal mesh, and soluble membrane.
[0060] To further improve the dissolution efficiency of flaky mortar during use, such as Figure 2 As shown, after the semi-dry granules are compressed into tablets, the tablets can be dried to remove residual solvent from the slurry and obtain slurry.
[0061] Specifically, in step S200, the drying temperature is controlled to be 50-120℃.
[0062] Further, in step S200, the drying temperature can be controlled to be 65-110℃.
[0063] To improve the preparation convenience of the wet mixture, in step S100, the wet mixture can be obtained by mixing the dry mixture and the binder solution, the dry mixture comprising inorganic cementitious material and aggregate, and the binder solution comprising water-soluble binder and solvent.
[0064] To improve the performance of the sheet mortar, the dry mixture can further comprise at least one of admixture, additive and fiber.
[0065] Specifically, the dry mixture comprises the following raw materials in parts by weight: 15-70 parts by weight of inorganic cementitious material, 15-85 parts by weight of aggregate, 0-50 parts by weight of admixture, 0-15 parts by weight of additive and 0-5 parts by weight of fiber.
[0066] Specifically, the inorganic cementitious material is at least one of cement, gypsum, lime, geopolymer, calcium silicate-based mineral;
[0067] The aggregate is at least one of natural sand, machine-made sand, expanded perlite, vitrified microbead, hollow glass bead, foamed resin particle, and expanded clay;
[0068] The admixture is at least one of fly ash, slag powder, carbide slag powder, calcined kaolin, coal gangue, silica fume, zeolite powder, desulfurization gypsum, limestone powder, steel slag powder, and phosphorous slag powder;
[0069] The additive is at least one of water retaining agent, redispersible latex powder, early strength agent, retarder, accelerator, water repellent agent, water reducing agent, antifreezing agent, disintegrant, expanding agent, shrinkage reducing agent, alkaline activator, acid activator; preferably, the water retaining agent is at least one of methyl cellulose, hydroxyethyl cellulose, carboxyethyl methyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, etc.; the redispersible latex powder is at least one of ethylene-vinyl acetate copolymer, ethylene-chloroethylene-vinyl laurate terpolymer, vinyl acetate-ethylene-higher fatty acid vinyl ester terpolymer, vinyl acetate-acrylate-higher fatty acid vinyl ester terpolymer, etc.; the early strength agent is at least one of chloride salt, sulfate salt, carbonate salt, nitrate salt, nitrite salt, sodium silicate, triethanolamine, triisopropanolamine, calcium formate, sodium acetate, etc.; the retarder is at least one of monosaccharide, polysaccharide, hydroxycarboxylic acid and its salt, polyhydric alcohol and its derivative, organic phosphoric acid and its salt, phosphate salt, zinc salt, boric acid and its salt, fluorosilicate, etc.; the accelerator is at least one of sodium aluminate, potassium aluminate, sodium carbonate, potassium carbonate, water glass, low-alkali or non-alkali accelerator, etc.; the water repellent agent is at least one of chloride salt, aluminum salt, silicate salt, stearate salt, organosilicon, metal soap, rubber emulsion, resin emulsion, etc.; the water reducing agent is at least one of polycarboxylic acid type water reducing agent, naphthalene type water reducing agent, anthracene type water reducing agent, aminosulfonate type, aliphatic hydroxyl sulfonate type, melamine, lignin sulfonate, humic acid, etc.; the antifreezing agent is at least one of nitrite salt, chloride salt, formamide, calcium oxalate, sodium acetate, etc.; the disintegrant is at least one of microcrystalline cellulose, low-substitution hydroxypropyl cellulose, carboxymethyl cellulose calcium, sodium carboxymethyl starch, hydroxypropyl starch, hydroxypropyl distarch phosphate, copolyvidone, alginate, etc.; the expanding agent is at least one of calcium sulphoaluminate, magnesium oxide, calcium oxide, iron oxide, etc.; the shrinkage reducing agent is at least one of monohydric alcohol, dihydric alcohol, amino alcohol, polyethylene oxide, polyether, etc.
[0070] The fiber is at least one of carbon fiber, glass fiber, steel fiber and polymer fiber.
[0071] The rheological property (flowability, consistency, viscosity) of the slurry is seriously affected, and the slurry cannot be smoothly extruded into a shape when the state of the slurry changes slightly; the slurry is easily blocked in the molding die when the consistency is large, and the slurry is easily layered and separated (solid-liquid two-phase separation) when the consistency is small; and the rheological property of the slurry changes significantly when the types and proportions of raw materials change slightly, thereby resulting in poor production fluency of the sheet-shaped mortar and poor stability of the product; the weight ratio of the dry mixture and the binder solution is 100:3-20.
[0072] To facilitate granulation and ensure the strength of the wet granules, the weight ratio of the water-soluble binder and the solvent in the binder solution can be controlled to be 1:2-75. By controlling the amount of the water-soluble binder, the prepared wet granules have sufficient strength (through the above-mentioned proportioning, the water-soluble binder can be decomposed from the granular state into the small molecular state, and the water-soluble binder can have good diffusion capacity in the gap between the dry mixed materials, and a dense binder network can be formed), so as to facilitate subsequent drying and tabletting.
[0073] Specifically, the solvent is an organic solvent or a mixture of an organic solvent and water.
[0074] Specifically, the solvent is a mixture of an organic solvent and water, and the weight ratio of the organic solvent to water is 1:0-3.
[0075] Specifically, the water-soluble binder is at least one of vegetable glue, animal glue, microbial glue, modified starch, modified cellulose, polymeric water-soluble resin, and condensation type water-soluble resin.
[0076] Specifically, the water-soluble binder is at least one of maltitol, maltodextrin, hydroxyethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyethylene oxide, and polyethylene glycol.
[0077] Specifically, in step S100, the granulation is any one of extrusion granulation, rotary granulation, and fluidized bed granulation.
[0078] Example 1:
[0079] A sheet mortar, the raw materials of which include:
[0080] Dry mixed material: 28 parts by weight of Portland cement, 65 parts by weight of mountain sand, 5 parts by weight of fly ash, 1.2 parts by weight of acrylic-styrene copolymer (redispersible latex powder), and 0.4 parts by weight of methyl cellulose (water retaining agent),
[0081] Water-soluble binder: 0.4 parts by weight of polyethylene glycol and 6 parts by weight of ethanol;
[0082] The sheet mortar is prepared by a preparation method comprising the following steps,
[0083] (1) mixing, mixing the dry mixed material and the binder solution to obtain a wet mixed material;
[0084] (2) granulation: the wet mixed material is granulated into wet granules with a particle size of 0.85-2.00 mm by an extrusion method;
[0085] (3) primary drying: the wet granules are dried at 70°C until the solvent residue rate is 1%, to obtain wet granules with a bulk density of 1200 kg / m 3a semi-dry granule, wherein the particle size distribution of the semi-dry granule is that the mass percentage of the semi-dry granule with a particle size of 0.85mm-1.40mm is 60%, and the mass percentage of the semi-dry granule with a particle size of 1.40mm-2.00mm is 40%;
[0086] (4) tabletting: tabletting the semi-dry granule to obtain a tablet body;
[0087] (5) secondary drying: drying the tablet body to remove residual solvent to obtain a tablet-shaped mortar.
[0088] Example 2:
[0089] A tablet-shaped mortar, the raw materials comprising:
[0090] dry mixture: 20 parts by weight of sulphoaluminate cement, 75 parts by weight of iron tailings machine-made sand, 8 parts by weight of sulphur gypsum, 0.9 parts by weight of ethylene-vinyl acetate copolymer (redispersible latex powder), 0.3 parts of carboxymethyl hydroxyethyl cellulose (water retaining agent),
[0091] water-soluble binder: 0.5 parts by weight of polyethylene glycol, 1 part by weight of water, 6 parts by weight of ethanol;
[0092] The tablet-shaped mortar is prepared by a preparation method comprising the following steps,
[0093] (1) mixing, mixing the dry mixture and the binder solution to obtain a wet mixture;
[0094] (2) granulation: the wet mixture is granulated into wet granules with a particle size of 0.85mm-2.00mm by extrusion method;
[0095] (3) primary drying: the wet granules are dried at 70°C to a solvent residual rate of 1.5% to obtain semi-dry granules with a bulk density of 1300kg / m 3 , wherein the particle size distribution of the semi-dry granule is that the mass percentage of the semi-dry granule with a particle size of 0.85mm-1.40mm is 30%, and the mass percentage of the semi-dry granule with a particle size of 1.40mm-2.00mm is 70%;
[0096] (4) tabletting: tabletting the semi-dry granule to obtain a tablet body;
[0097] (5) secondary drying: drying the tablet body to remove residual solvent to obtain a tablet-shaped mortar.
[0098] Example 3:
[0099] A tablet-shaped mortar, which is different from Example 1, the wet mixture is granulated into wet granules with a particle size of 2.00mm-4.80mm by extrusion method; in addition, the bulk density of the semi-dry granule used for tabletting is 1500kg / m 3The particle size distribution of the semi-dry granules is as follows: the mass percentage of semi-dry granules with a particle size of 2.00mm-2.80mm is 20%, the mass percentage of semi-dry granules with a particle size of 2.80mm-4.00mm is 40%, and the mass percentage of semi-dry granules with a particle size of 4.00mm-4.75mm is 40%.
[0100] Example 4:
[0101] A sheet-shaped mortar, different from Example 1, is prepared by extrusion of the wet mixture into wet granules with a particle size of 2.00mm-4.80mm. In addition, the bulk density of the semi-dry granules used for tabletting is 1800kg / m 3 The particle size distribution of the semi-dry granules is as follows: the mass percentage of semi-dry granules with a particle size of 2.00mm-2.80mm is 20%, the mass percentage of semi-dry granules with a particle size of 2.80mm-4.00mm is 15%, and the mass percentage of semi-dry granules with a particle size of 4.00mm-4.75mm is 65%.
[0102] Example 5:
[0103] A sheet-shaped mortar, different from Example 2, is prepared by tabletting of the semi-dry granules with a bulk density of 1050kg / m 3 The particle size distribution of the semi-dry granules is as follows: the mass percentage of semi-dry granules with a particle size of 0.85mm-1.40mm is 80%, and the mass percentage of semi-dry granules with a particle size of 1.40mm-2.00mm is 20%.
[0104] Comparative Example 1:
[0105] A sheet-shaped mortar, different from Example 1, is prepared by tabletting of the wet mixture obtained in the preparation process, which specifically comprises the following steps:
[0106] (1) mixing, mixing the dry mixture and the binder solution to obtain a wet mixture;
[0107] (2) tabletting: tabletting the wet mixture to obtain tablets;
[0108] (3) drying: drying the tablets to obtain a sheet-shaped mortar.
[0109] Comparative Example 2:
[0110] A sheet-shaped mortar, different from Example 2, is prepared by the preparation method in Comparative Example 1.
[0111] Comparative Example 3:
[0112] A sheet-shaped mortar, different from Example 3, is prepared by the preparation method in Comparative Example 1.
[0113] Comparative Example 4:
[0114] A sheet-shaped mortar, distinguished from Example 4, is prepared by the preparation method in Comparative Example 1.
[0115] Comparative Example 5:
[0116] A sheet-shaped mortar, distinguished from Example 5, is prepared by the preparation method in Comparative Example 1.
[0117] The sheet-shaped mortar obtained in Examples 1-5 and the sheet-shaped mortar obtained in Comparative Examples 1-5 are subjected to performance testing, and the testing results are shown in Table 1,
[0118] Table 1 Performance testing table of sheet-shaped mortar
[0119]
[0120]
[0121] The dissolving time limit testing method is as follows: 750 mL of water is placed in a 1000 mL beaker, the water temperature is 20±5℃, a magnetic stirrer is placed, a square mesh screen with a hole diameter of 5.5 mm is horizontally installed at the 500 mL scale in the beaker, and the square mesh screen is clamped tightly with the inner wall of the beaker. The beaker is placed on the magnetic stirrer, and the rotation speed is set to 500 revolutions / minute. The test sample specification is a cube of dry mortar with a side length of 30mmx30mmx3mm, which is dried at 60℃ for 24 hours before testing. The sample is gently placed in the beaker, and the stopwatch is started at the same time. When the dissolved slurry completely penetrates the square mesh screen (where the support body, fiber, and large particle aggregate can not pass), stop the timer. The time recorded at this time is the dissolving time limit of the test sample, and the unit is second (s).
[0122] The 28d compressive strength and 14d tensile bonding strength after hardening are determined according to the standard JGJ / T 70-2009 "Building Mortar Basic Performance Test Method". When measuring, the sheet-shaped dry mortar is crushed in advance, and after removing the support body, it is mixed with water to form a slurry with a consistency of 85mm-90mm.
[0123] From the above table, it can be seen that the dissolving efficiency of the sheet-shaped mortar prepared by the present application is effectively improved, and the mechanical strength is basically unchanged.
[0124] Example 6:
[0125] A sheet-shaped mortar, raw materials including:
[0126] Dry mixture: 70 parts by weight of cement, 15 parts by weight of vitrified microbeads, 14.3 parts by weight of steel slag powder, and 0.7 parts by weight of antifreeze agent;
[0127] Water-soluble binder: 1 part by weight of sodium alginate, 4 parts by weight of water, and 15 parts by weight of ethanol;
[0128] The flaky mortar is prepared by a preparation method comprising the following steps,
[0129] (1) mixing, mixing the dry mixture and the binder solution to obtain a wet mixture;
[0130] (2) granulation: the wet mixture is granulated into wet particles with a particle size of 0.85mm-2.0mm by an extrusion method;
[0131] (3) first drying: the wet particles are dried at 50℃ to a solvent residual rate of 10% to obtain semi-dry particles; the semi-dry particles are sieved to obtain semi-dry particles with a bulk density of 1350kg / m 3 , a particle size distribution of 55% of semi-dry particles with a particle size of 0.85mm-1.40mm, and 45% of semi-dry particles with a particle size of 1.40mm-2.00mm;
[0132] (4) tabletting: the semi-dry particles are tabletted to obtain tablets;
[0133] (5) second drying: the tablets are dried to remove residual solvent to obtain the flaky mortar.
[0134] Example 7:
[0135] A flaky mortar, different from example 6, in the first drying process, the wet particles are dried at 65℃ to a solvent residual rate of 5% to obtain semi-dry particles; the semi-dry particles are sieved to obtain semi-dry particles with a bulk density of 950kg / m 3 , a particle size distribution of 45% of semi-dry particles with a particle size of 0.85mm-1.40mm, and 55% of semi-dry particles with a particle size of 1.40mm-2.00mm.
[0136] Example 8:
[0137] A flaky mortar, different from example 6, in the first drying process, the wet particles are dried at 75℃ to a solvent residual rate of 1% to obtain semi-dry particles; the semi-dry particles are sieved to obtain semi-dry particles with a bulk density of 900kg / m 3 , a particle size distribution of 42% of semi-dry particles with a particle size of 0.85mm-1.40mm, and 58% of semi-dry particles with a particle size of 1.40mm-2.00mm.
[0138] Example 9:
[0139] A flaky mortar, raw materials comprising:
[0140] dry mixture: a mixture of 50 parts by weight of cement, gypsum and lime, a mixture of 85 parts by weight of natural sand and machine-made sand, 50 parts by weight of calcined kaolin, 15 parts by weight of redispersible latex powder, and 5 parts by weight of carbon fiber;
[0141] Water-soluble binder: 0.5 parts by weight of polyethylene glycol, 12.5 parts by weight of water, 25 parts by weight of ethanol;
[0142] The flaky mortar is prepared by a preparation method comprising the following steps,
[0143] (1) mixing, mixing the dry mixture and the binder solution to obtain a wet mixture;
[0144] (2) granulation: the wet mixture is granulated into wet granules with a particle size of 2.00-4.80 mm by an extrusion method;
[0145] (3) first drying: the wet granules are dried at 110°C to a solvent residual rate of 2% to obtain semi-dry granules; the semi-dry granules are sieved to obtain semi-dry granules with a bulk density of 1400 kg / m 3 , a particle size distribution of 22% of semi-dry granules with a particle size of 2.00-2.80 mm, 50% of semi-dry granules with a particle size of 2.80-4.00 mm, and 28% of semi-dry granules with a particle size of 4.00-4.75 mm;
[0146] (4) tabletting: the semi-dry granules are tabletted to obtain tablets;
[0147] (5) second drying: the tablets are dried to remove residual solvent to obtain the flaky mortar.
[0148] Example 10:
[0149] A flaky mortar, different from example 9, in the first drying process, the wet granules are dried at 80°C to a solvent residual rate of 1% to obtain semi-dry granules; the semi-dry granules are sieved to obtain semi-dry granules with a bulk density of 1340 kg / m 3 , a particle size distribution of 25% of semi-dry granules with a particle size of 2.00-2.80 mm, 40% of semi-dry granules with a particle size of 2.80-4.00 mm, and 35% of semi-dry granules with a particle size of 4.00-4.75 mm.
[0150] The above only describes preferred embodiments of the present application and is not intended to limit the present application, and any modification, equivalent replacement, and improvement made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing sheet mortar, characterized in that, Includes the following steps: Step S100: Obtain a wet mixture, wherein the raw materials of the wet mixture include inorganic cementitious materials, aggregates, water-soluble binders and solvents; granulate the wet mixture to obtain wet granules; Step S200: Dry the wet granules to obtain semi-dry granules; Step S300: The semi-dry particles are sieved to obtain particles with a diameter of 0.85mm to 4.75mm. The semi-dry particles are then compressed into flakes. The particle size distribution of the semi-dry particles is either a first particle size combination or a second particle size combination. In the first particle size combination, semi-dry particles with a diameter of 0.85mm to 1.40mm account for 30 to 80 parts by weight, and semi-dry particles with a diameter of 1.40mm to 2.00mm account for 20 to 70 parts by weight. In the second particle size combination, semi-dry particles with a diameter of 2.00mm to 2.80mm account for 20 to 60 parts by weight, semi-dry particles with a diameter of 2.80mm to 4.00mm account for 15 to 50 parts by weight, and semi-dry particles with a diameter of 4.00mm to 4.75mm account for 25 to 65 parts by weight, resulting in flake mortar.
2. The preparation method according to claim 1, characterized in that, The residual solvent in the semi-dry particles has a weight percentage of 1% to 10%.
3. The preparation method according to claim 1, characterized in that, In step S300, the bulk density of the semi-dry particles is 900 kg / m³. 3 ~1800kg / m 3 .
4. The preparation method according to claim 3, characterized in that, In step S300, the bulk density of the semi-dry particles is 1100 kg / m³. 3 ~1500kg / m 3 .
5. The preparation method according to claim 1, characterized in that, In step S300, the semi-dry granules and the support are compressed together into tablets.
6. The preparation method according to claim 5, characterized in that, The support is located on the lower and / or upper surface of the sheet mortar.
7. The preparation method according to claim 5, characterized in that, The support is at least one of inorganic fiber mesh, polymer mesh, metal mesh, and soluble membrane.
8. The preparation method according to claim 5, characterized in that, After the semi-dry granules are compressed into sheets, they are dried to obtain sheet mortar.
9. The preparation method according to claim 1, characterized in that, In step S200, the drying temperature is 50℃~120℃.
10. The preparation method according to claim 9, characterized in that, In step S200, the drying temperature is 65℃~110℃.
11. The preparation method according to claim 1, characterized in that, In step S100, a wet mixture is obtained by mixing a dry mixture and an adhesive solution. The dry mixture includes inorganic cementitious materials and aggregates, and the adhesive solution includes water-soluble adhesives and solvents.
12. The preparation method according to claim 11, characterized in that, The dry mix also includes at least one of admixtures, additives, and fibers.
13. The preparation method according to claim 11, characterized in that, The dry mix comprises the following raw materials in parts by weight: 15 to 70 parts by weight of inorganic cementitious materials, 15 to 85 parts by weight of aggregates, 0 to 50 parts by weight of admixtures, 0 to 15 parts by weight of additives, and 0 to 5 parts by weight of fibers.
14. The preparation method according to claim 13, characterized in that, The inorganic cementitious material is at least one of cement, gypsum, lime, geopolymer, and calcium silicate-based minerals. The aggregate is at least one of the following: natural sand, manufactured sand, expanded perlite, vitrified microspheres, hollow glass beads, foamed resin particles, and expanded clay. The admixture is at least one of the following: fly ash, slag powder, calcium carbide slag powder, calcined kaolin, coal gangue, silica fume, zeolite powder, desulfurized gypsum, limestone powder, steel slag powder, and phosphorus slag powder. The additive is at least one of the following: water-retaining agent, redispersible latex powder, early strength agent, retarder, quick-setting agent, waterproofing agent, water-reducing agent, antifreeze agent, disintegrant, expanding agent, shrinkage reducing agent, alkaline activator, and acidic activator. The fiber is at least one of carbon fiber, glass fiber, steel fiber, and polymer fiber.
15. The preparation method according to claim 11, characterized in that, The weight ratio of the dry mix to the adhesive solution is 100:3~20.
16. The preparation method according to claim 11, characterized in that, The weight ratio of water-soluble adhesive to solvent in the adhesive solution is 1:2 to 75.
17. The preparation method according to claim 16, characterized in that, The solvent is an organic solvent or a mixture of an organic solvent and water.
18. The preparation method according to claim 16, characterized in that, The solvent is a mixture of an organic solvent and water, with a weight ratio of organic solvent to water of 1:0~3.
19. The preparation method according to claim 1, characterized in that, The water-soluble adhesive is at least one of plant gum, animal gum, microbial gum, modified starch, modified cellulose, polymeric water-soluble resin, and condensation water-soluble resin.
20. The preparation method according to claim 1, characterized in that, In step S100, the granulation is any one of extrusion granulation, rotary granulation, or fluidized bed granulation.
21. A sheet-like mortar, characterized in that, Prepared by the preparation method according to any one of claims 1 to 20.
Citation Information
Patent Citations
Thermal insulation fire-proof aggregate with polystyrene particle-coated expanded and vitrified bead mortar and preparation method thereof
CN102167529A
Preparation process of flaky dry mortar
CN110818336A